A new DFT-based frequency estimation algorithm for protection devices under normal and fault conditions - Soroush Karimi Madahi, Seyed; Askarian Abyaneh, Hossein; Alberto Nucci, Carlo; Parpaei, Mohammad (International journal of electrical power & energy systems, 2022)
•Proposing a new DFT-based algorithm to estimate power system frequency under normal and fault conditions.•Designing an optimization-based filter to eliminate harmonics.•Presenting a new method to mitigate the effects of decaying DC under off-nominal conditions. Frequency is one of the essential parameters for monitoring, control, and protection in power systems. Some protection devices use frequency for deciding under various conditions of the power system. Therefore, it is important to estimate frequency rigorously and fast. In this paper, a DFT- based algorithm is introduced for frequency estimation in the presence of harmonics and decaying DC. Initially, According to the condition of the power system, the type of input signal (current or voltage) is determined. The current and voltage signals are the input to the proposed algorithm under fault and normal conditions, respectively. Based on the type of the input signal, the frequency estimation method (FEM) is selected and used. 2 FEMs are proposed to estimate the frequency based on solving a cubic equation. For both FEMs, an optimization-based filter is designed and applied to mitigate harmonics. The proposed algorithm is validated under various static and dynamic tests in MATLAB. The results show that the proposed algorithm is accurate and fast with a low computational burden.